A new process for simultaneous production of tannase and phytase by Paecilomyces variotii in solid-state fermentation of orange pomace - Madeira, Jose Valdo; Macedo, Juliana Alves; Macedo, Gabriela Alves (Bioprocess and biosystems engineering, 2012)
The production of enzymes such as tannases and phytases by solid-state fermentation and their use in animal feed have become a subject of great interest. In the present work, Paecilomyces variotii was used to produce tannase and phytase simultaneously. Solid-state fermentation, a process initially designed for tannase production, was implemented here using orange pomace as substrate. Orange pomace is the waste product of the large orange juice industry in Brazil, and it has also been used as an ingredient in animal feed. In addition to enzymatic production, biotransformation of the phenolic content and antioxidant capacity of the orange pomace were analyzed after fermentation. Fermentation conditions, namely moisture level and tannic acid concentration rate, were studied using CCD methodology. The response surface obtained indicated that the highest tannase activity was 5,000 U/gds after 96 h at 59% (v/w) and 3% (w/w) and that of phytase was 350 U/gds after 72 h at 66% (v/w) and 5.8% (w/w) of moisture level and tannic acid concentration, respectively. The amount of tannase production was similar to the levels achieved in previous studies, but this was accomplished with a 7% (w/w) reduction in the amount of supplemental tannic acid required. These results are the first to show that P. variotii is capable of producing phytase at significant levels. Moreover, the antioxidant capacity of orange pomace when tested against the free radical ABTS was increased by approximately tenfold as a result of the fermentation process.